Rancang Bangun Website Member Cuci Sepatu Menerapkan Metode Waterfall - Naufal Ariesta Zildjian; Rauhulloh Ayatulloh Khomeini Noor Bintang (TIN: Terapan Informatika Nusantara, 2026)
The current development of the shoe cleaning service industry demands efficiency and transparency in service, but operations at Alwayscleanhoes Shoes in Karanganyar are still carried out manually. The recording process via instant messaging risks data loss and irregular transaction history. This research intends to devise and develop a member-backed footwear laundering operation intelligence system utilizing the Laravel infrastructure and MySQL data repository. The platform evolution technique applied constitutes the Waterfall paradigm, which encompasses the phases of necessity evaluation, architectural planning, execution (building), alongside examination. This system is designed to centralize customer data management, order automation, and real-time tracking features for work status. System testing was conducted through the User Acceptance Testing (UAT) method with 10 respondents consisting of admins, regular customers (members), the general public, and technical experts. The findings indicated that the deployment of this online platform effectively streamlined the functional workflow and facilitated consumers to approach utilities autonomously. Based on a Likert scale analysis, the UAT test resulted in a score percentage of 88.67%, indicating that the system is in the "Very Good" category and is worthy of full implementation. This research provides a practical contribution to improving service quality and data management accuracy at Alwayscleanhoes Shoes.